Regenerative Approaches Using Platelet-Rich Plasma (PRP) and Stem Cells for Pelvic Floor Disorders: A Systematic Review - Devanti Octavia Ellyamurti; Griffin Mia Inggita Kusno; Tuti Khairani Rahman; Putri Dhiya Prameswari Woyono (Medicinus, 2026)
Background: Pelvic floor disorders, including stress urinary incontinence, pelvic organ prolapse, fecal incontinence, and vulvovaginal atrophy, represent a major burden on quality of life. Platelet-rich plasma and platelet-rich fibrin have emerged as autologous regenerative therapies with potential applications across these conditions. This systematic review synthesized the clinical evidence from human trials of platelet-rich plasma and platelet-rich fibrin for pelvic floor disorders to evaluate efficacy, safety, and methodological quality. Methods: PubMed, EMBASE, and Scopus were searched from inception through 15 May 2026. Eligible studies were human clinical trials of platelet-rich plasma or platelet-rich fibrin injection for pelvic floor disorders or closely related urogynecologic conditions reporting continence, functional, quality-of-life, or safety outcomes. Study selection was performed independently by all authors, with discrepancies resolved through discussion. Risk of bias was assessed using the Cochrane Risk of Bias 2 tool for randomized trials and the Risk of Bias in Non-Randomized Studies of Interventions tool for observational studies. Result: Fourteen studies (663 participants) were included, comprising six randomized trials and eight prospective nonrandomized or single-arm studies. The majority addressed female stress urinary incontinence. Randomized controlled trials demonstrated significant improvements in continence questionnaires and pad tests favoring platelet-rich plasma over sham or pelvic floor muscle training. However, one placebo-controlled trial found no significant difference. Safety profiles were favorable across all studies. Risk of bias was high in single-arm studies and ranged from some concerns to low in randomized trials. Conclusions: Platelet-rich plasma and platelet-rich fibrin demonstrate preliminary safety and efficacy signals for pelvic floor disorders, particularly stress urinary incontinence. However, the evidence base remains limited by small sample sizes, heterogeneous protocols, and a predominance of uncontrolled studies, warranting larger, well-designed randomized controlled trials.